Modernization of African food retailing and (un)healthy food consumption: Insights from Zambia - Makaiko G. Khonje; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2019)
Food environments in Africa are changing rapidly, with modern retailers - such as supermarkets, hypermarkets, and fast-food restaurants - gaining in importance. Changing food environments can influence consumer food choices and dietary patterns. Recent research suggested that the growth of supermarkets leads to more consumption of processed foods, less healthy diets, and rising obesity. However, the use of modern retailers may differ by socioeconomic status, which was hardly considered in previous work. Furthermore, existing studies on nutrition effects focused mainly on the role of supermarkets, although most consumers obtain their food from various sources. We add to this research direction by examining more explicitly the relationships between socioeconomic status, use of different modern and traditional retailers, and dietary patterns. The analysis uses household survey data from urban Zambia. Results show that twothirds of the households use modern and traditional retailers simultaneously, whereby richer households are more likely than poorer households to use supermarkets and hypermarkets. Use of modern retailers is positively associated with higher consumption of ultra-processed foods, also after controlling for income and other socioeconomic factors. However, the use of traditional grocery stores and kiosks is also positively associated with the consumption of ultra-processed foods, suggesting that modern retailers are not the only drivers of dietary transitions.
Keywords: 330; retail modernization; supermarkets; food consumption; diets; nutrition transition; Zambia